Hubungan Kehilangan Gigi Terhadap Kualitas Hidup Pada Lanjut Usia : Scoping Review - Resa Ferdina; Leny Sang Surya; Nabila Sasqia (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2022)
Tooth loss affects social activities and causes discomfort and will interfere with various aspects of daily life such as talking, eating, drinking, socializing and self-confidence. Tooth loss has an impact on individual emotions, interpersonal relationships and daily activities so that overall it will affect a person's quality of life. The purpose of this scoping review study was to determine the relationship between tooth loss and quality of life in the elderly. The method used in this research is the literature study method. There are 12 data articles obtained through database searches consisting of 4 Google Scholar, 5 Pubmed and 3 Science Direct. The results of this scoping review found a significant relationship between tooth loss and quality of life related to oral health in the elderly, using OHRQOL and GOHAI measurements as instruments. The conclusion of this scoping review is that tooth loss with quality of life in the elderly has a very large impact such as lack of self-confidence, difficulty in choosing food, decreased masticatory efficiency, overload on supporting tissues, and difficulty in speaking.